Prevalence and Spatial Distribution of Cephenemyia stimulator in Roe Deer (Capreolus capreolus) from the North of Spain and Portugal - Néstor Martínez-Calabuig; Madalena Vieira-Pinto; Ana Saldaña; Rosario Panadero; José Aranha (Insects)
Since the first documented case of Cephenemyia stimulator in Spain in 2001, this myiasis has experienced rapid expansion, with the first case also detected in 2021 in Portugal. Between January 2020 and October 2024, a study was carried out in northern Spain (Cantabria, Galicia, País Vasco and Principado de Asturias) and Portugal (Bragança, Viana do Castelo and Vila Real) to evaluate the presence and distribution of this myiasis in these areas. The prevalence of infestation was 76.6 ± 4.72% (95% CI) and 38.78 ± 13.78% (95% CI), with a mean intensity of 62.27 ± 104.40 and 37.74 ± 36.84 larvae per animal in Spain and Portugal, respectively. Regarding age, larval intensity was significantly higher in young animals (109.76 ± 148.59) than in adults (32.22 ± 39.01) and old animals (33.64 ± 34.21) (p < 0.05). These results reflect a large increase in the prevalence and importance of younger animals in the spread of the disease. Therefore, it is very important to control and manage populations, focusing on the youngest animals.